Gifts and Nationalism in Wartime Japan - Minowa, Yuko and Belk, Russell W. (Journal of Macromarketing, 2018)
This study investigates the shifting discourse and visual rhetoric of consumer rituals in the cultural media during wartime. Specifically, we examine Japanese newspaper advertisements for seasonal gifts and sympathy gifts in urban cities published between 1937 and 1940. This research addresses two questions: (1) how were advertising arguments constructed justifying spending for gifts while instructing readers on being thrifty during the wartime material shortages, and (2) how was the consumer ritual practice of gift giving used to propagate nationalism? The results of our iconographic-semiotic analysis show four advertising themes: compatibility with national policy, timeliness under the wartime circumstances, empathy with families whose members were serving at the front, and sympathy with those serving at the front. The advertisements enhanced nationalism in two ways: (1) through the promotion of nationalistic gift giving, and (2) by appealing to patriotism, which involves emotionally laden nationalistic sentiments.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMjc2MTQ2NzE4NzczNDcz